2020
DOI: 10.1515/tnsci-2020-0140
|View full text |Cite
|
Sign up to set email alerts
|

BDMC protects AD in vitro via AMPK and SIRT1

Abstract: BackgroundAlzheimer’s disease (AD) is a common neurodegenerative disorder without any satisfactory therapeutic approaches. AD is mainly characterized by the deposition of β-amyloid protein (Aβ) and extensive neuronal cell death. Curcumin, with anti-oxidative stress (OS) and cell apoptosis properties, plays essential roles in AD. However, whether bisdemethoxycurcumin (BDMC), a derivative of curcumin, can exert a neuroprotective effect in AD remains to be elucidated.MethodsIn this study, SK-N-SH cells were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Moreover, the pathological processes triggered by Aβ deposition promote further deposition, leading to a response cascade. It has also been reported that Aβ is neurotoxic, thus inducing nerve cell apoptosis and, in turn, impairing cognitive function [ 46 , 47 ]. Abnormalities in the cholinergic system in AD also induce abnormal amyloid precursor protein metabolism and tau phosphorylation, resulting in neurotoxicity, neuroinflammation, and apoptosis [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pathological processes triggered by Aβ deposition promote further deposition, leading to a response cascade. It has also been reported that Aβ is neurotoxic, thus inducing nerve cell apoptosis and, in turn, impairing cognitive function [ 46 , 47 ]. Abnormalities in the cholinergic system in AD also induce abnormal amyloid precursor protein metabolism and tau phosphorylation, resulting in neurotoxicity, neuroinflammation, and apoptosis [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…no. HY-15452; MedChemExpress) at 37˚C, followed by LPS induction and propofol treatment ( 18 , 19 ). Untreated H9C2 cells were regarded as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…According to the manufacturer’s instructions, the total RNA of the mouse cortex and hippocampus was isolated with TRIzol reagent, and then cDNA was obtained by reverse transcription. qRT-PCR was performed as previously described [ 33 ]. Calculations were measured using the 2 −ΔΔCt method to analyze the relative expression of each gene, and the bar chart was drawn using GraphPad Prism 5.0.…”
Section: Methodsmentioning
confidence: 99%